ROLE OF METASUBJECT EDUCATIONAL RESULTS IN LEARNERS’ PROFESSIONAL SELF-CONSCIOUSNESS FORMATION - Maria A. Isaikina (Science and Innovation Center Publishing House, 2021)
The article reveals the notion of metasubject educational results that are closely connected with the formation of universal skills necessary for a specialist in demand in the contemporary society.